The Domination of White People Toward Chinese People in Linda Sue Park’s Prairie Lotus - Triswandari, Ika Novieyanti; Hartanto, Erika Citra Sari; Wenanda, Diva; Ayuningtias, Diah Ikawati (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2024)
This study aims to find out the dominance of white people in the novel Prairie Lotus and the impact that occurs after the emergence of the domination in the novel. This study uses a qualitative descriptive research method. The data from this study is the conversation of the characters and the narrators’ narration. The method of collecting data from this study is to read the entire contents of the novel using close reading techniques. In analyzing the data, the writer uses the theory of race and racism by Robert Miles and Malcolm Brown. The results show that white people dominate the way of life of minorities in this novel, namely Hanna. She gets a lot of oppression from white people in the Dakota area. This study also shows that there is an impact received by the main character in the novel 'Prairie Lotus', namely the impact on her psyche and mental health. The emergence of domination is due to the lack of an immediate sense of brotherhood and tolerance towards people from the same regions around the main character's residence in the novel Prairie Lotus.